2014
DOI: 10.2147/dmso.s72695
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoleic acid reduces intramuscular lipid and restores insulin sensitivity in obese sheep

Abstract: Obese sheep were used to assess the effects of palmitoleic (C16:1 cis-9) acid infusion on lipogenesis and circulating insulin levels. Infusion of 10 mg/kg body weight (BW)/day C16:1 intravenously in obese sheep reduced (P<0.01) weight gain by 77%. Serum palmitoleic levels increased (P<0.05) in a linear manner with increasing levels of C16:1 infusion. Cis-11 vaccenic (C18:1 cis-11) acid, a known elongation product of palmitoleic acid, was also elevated (P<0.05) in serum after 14 days and 21 days of infusion. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 31 publications
3
38
0
2
Order By: Relevance
“…However, palmitoleate is relatively more abundant in adipose tissue than it is in serum. In animals, infusion of cis-palmitoleate increases the content of cis-palmitoleate in subcutaneous and mesenteric adipose tissue, longissimus and semitendinosus muscles, and the liver (59). This means that increasing circulating palmitoleate influences tissue abundance.…”
Section: Where Is Palmitoleate Hidden?mentioning
confidence: 99%
“…However, palmitoleate is relatively more abundant in adipose tissue than it is in serum. In animals, infusion of cis-palmitoleate increases the content of cis-palmitoleate in subcutaneous and mesenteric adipose tissue, longissimus and semitendinosus muscles, and the liver (59). This means that increasing circulating palmitoleate influences tissue abundance.…”
Section: Where Is Palmitoleate Hidden?mentioning
confidence: 99%
“…Insulin resistance, glucose uptake, liver inflammation ( IL-1β); all independent of PPARα [83] Obese sheep, iv infusion of palmitoleic acid (10 mg kg −1 d −1 ), 28 d Weight gain, plasma cis-vaccenic acid, insulin, total lipid content (ST muscle, MAT), mRNA for ACC, ELOVL6, and AMPK in liver, sub-AT, and ST muscle, mRNA for GLUT4 and CPT1B (sub-AT, liver) [15] Primary BMDM from HFD mice, palmitic and/or palmitoleic acids 750 μM (6 h) NO, cytokine secretion, mRNA for CXCL1, IL-6, TNF, NOS2, mRNA MCP-1, TGFb1, IL-10, IκBα degradation and NFκB translocation; required AMPK [51] Liver of mice on HFD, fed palmitoleic acid (300 mg kg…”
Section: Referencementioning
confidence: 99%
“…[82] Similar to in vitro studies, intravenous palmitoleic acid infusion (10 mg kg −1 body weight d −1 ) upregulated AMPK expression in liver, subcutaneous adipose tissue, and muscle of obese sheep. [83] In addition, palmitoleic acid supplementation (300 mg kg −1 d −1 ) increased the phosphorylation of AMPK in liver of obese mice, [51] an effect that depends on the activation of the pro-oxidative transcription factor, PPARα (Table 5). …”
Section: Wwwadvancedsciencenewscom Wwwmnf-journalcommentioning
confidence: 99%
“…Our supplemental oil diets contained 4–5% supplemental oil (Table ) and are, therefore, below this threshold level. Previous studies in our laboratory used intravenous administration of the POA to avoid biohydrogenation (Duckett et al, ; Long et al, ), a normal process where dietary monounsaturated fatty acids (MUFA) and PUFA are hydrogenated to saturated fatty acids (SFA) to reduce toxicity of dietary lipids in ruminant animals like sheep. Based on the published biohydrogenation rates (78%, Sackmann et al, ; 84%, Duckett and Gillis, ; 87%, Atkinson et al, ) and digestibility values (78%, Glasser et al, ; 90%, Sklan et al, ; 84–89%, Atkinson et al, ), we estimate that the level of palmitoleic acid or ALA reaching the small intestine without biohydrogenation would be about 64–111 mg/kg BW.…”
Section: Methodsmentioning
confidence: 99%
“…Palmitoleic acid inhibits lipogenesis in bovine primary adipocyte cultures (Burns et al, , ). Intravenous infusion of palmitoleic acid (0–10 mg/kg body weight [BW]) to obese sheep reduces feed intake, BW gain, and insulin resistance in a dose‐dependent manner with higher dose levels resulting in a greater reduction (Duckett et al, ; Long et al, ). However, alterations in body composition during this short‐term study (28 days) were not observed, which may be related to the obese state (40% body fat) attained by mature lambs.…”
Section: Introductionmentioning
confidence: 99%